2012
DOI: 10.1080/08927014.2011.653562
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of HSA, IgG and laminin-1 on model hydroxyapatite surfaces – effects of surface characteristics

Abstract: Ellipsometry and mechanically assisted sodium dodecyl sulphate elution was utilized to study the adsorption of human serum albumin (HSA), human immunoglobulin G (IgG), laminin-1, as well as competitive adsorption from a mixture of these proteins on spin-coated and sintered hydroxyapatite (HA) surfaces, respectively. The HA surfaces were characterized concerning wettability and roughness by means of water contact angles and atomic force microscopy, respectively. Both surface types were hydrophilic, and the aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Large m-HAP particles cannot be digested by osteoblastic SaOS-2 cells. The more hydrophobic and less protein absorbed surfaces of m-HAP particles in the m-HAP/Col composite ( 27 ) may detach the SaOS-2 cells with time, rendering strange morphological changes, as observed in our study ( Fig. 7 ).…”
Section: Discussionsupporting
confidence: 60%
“…Large m-HAP particles cannot be digested by osteoblastic SaOS-2 cells. The more hydrophobic and less protein absorbed surfaces of m-HAP particles in the m-HAP/Col composite ( 27 ) may detach the SaOS-2 cells with time, rendering strange morphological changes, as observed in our study ( Fig. 7 ).…”
Section: Discussionsupporting
confidence: 60%
“…The predominance of one of them over the others is closely related to the type of protein and to the chemical–physical features of the inorganic surface. Based on our results and on previous works about HA functionalization with proteins, in this system, the hydrophobic interactions can be discarded and it can be assumed that mainly electrostatic interactions between LF and the HA surface take place.…”
Section: Discussionmentioning
confidence: 92%
“…Fan et al [ 61 ] used quartz crystal microbalance to determine the adsorption of bovine serum albumin (BSA) and Fib on the L- and D-selenocystine (L-Se/D-Se) immobilized TiO 2 films, and found that surface chirality led to different steric interactions between the negatively charged L-Se/D-Se surfaces and the negatively charged BSA and Fib, which in turn influenced hydrogen bonding and hydrophobic interaction, and eventually influenced protein adsorption. Svendsen et al [ 62 ] used ellipsometry to study the competitive adsorption of human serum albumin (HSA), human immunoglobulin G (IgG) and laminin-1 on the spin-coated and sintered hydroxyapatite (HA) surfaces. The results showed that the differences in surface roughness and chemical composition (the spin-coated HA surface contained titanium and aluminum, whereas the sintered surface contained sodium) between two types of HA substratum contributed to different adsorption properties of proteins.…”
Section: Resultsmentioning
confidence: 99%